2013
DOI: 10.1097/ta.0b013e31829a2c43
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical complications of intertrochanteric hip fractures treated with trochanteric femoral nails

Abstract: The most common mechanical complication was lateral migration of the helical blade; however, this rarely led to a clinical problem. Medial migration of the blade in the head without loss of reduction was the second most frequent complication. We have identified a new complication associated with the TFN, that is, medial perforation without loss of reduction. Blade migration in the head was less frequent when blades were placed inferiorly with a tip-apex distance of at least 15 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
73
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 24 publications
(23 reference statements)
11
73
4
Order By: Relevance
“…We observed axial migration of the helical blade although the blade shaft was allowed to slide freely in the test fixture. Clinical series of intertrochanteric fractures demonstrated similar failure mechanisms as observed in our study . Deficient lateral buttress and unstable calcar patterns as mimicked by our test setup, have been described as additional factors for nail toggling and medial migration in intertrochanteric fractures …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We observed axial migration of the helical blade although the blade shaft was allowed to slide freely in the test fixture. Clinical series of intertrochanteric fractures demonstrated similar failure mechanisms as observed in our study . Deficient lateral buttress and unstable calcar patterns as mimicked by our test setup, have been described as additional factors for nail toggling and medial migration in intertrochanteric fractures …”
Section: Discussionsupporting
confidence: 83%
“…Helical blades exhibited axial migration with joint perforation in clinical series and revealed a higher cutout rate compared to other implant designs. 12,[24][25][26] A previous biomechanical study reported different direction of the migration vector of helical blades in comparison to dynamic hip screws. 4 We observed a nearly equidistant cranial/vertical and axial migration of helical blades in our test setup.…”
Section: Tip-apex Distance Of Helical Bladesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, our study assumed that the long Gamma nail eliminated the risk of periprosthetic fracture; however, the original model of this implant was not free of complications, including periprosthetic fractures. In a study by Liu et al, 16 fracture at the tip of the TFN occurred in 1.3% of patients and was related to a new trauma. In a systematic review, on the occurrence of secondary fractures around intramedullary nails used to treat intertrochanteric hip fractures, Norris et al 15 reported the results from three data sets in which patients were treated with either a long or short TFN and there was no occurrence of secondary fractures.…”
Section: Discussionmentioning
confidence: 96%
“…A 2013 retrospective review reported a 9.4% incidence of lateral migration of greater than 1 cm. 8 Excessive lateral migration of the helical blade may cause hip pain with ambulation, iliotibial band irritation, or trochanteric bursitis, and some patients require blade exchange or hardware removal. Any complication that impedes mobilization or necessitates reoperation is significant.…”
mentioning
confidence: 99%